The danger of magnet attraction: an 11-year cohort of pediatric intestinal complications due to magnet ingestion - Varlıklı, Onursal; Akay, Mustafa Alper; Gürbüz Sarıkaş, Necla; Metin, Semih; Ekingen Yıldız, Gülşen (The Turkish Journal of Pediatrics, 2025)
Introduction. In recent years, there has been a significant rise in the number of pediatric cases involving multiple magnet ingestion, resulting in increased incidence and morbidity of injuries. When a metal object and magnet are ingested, either single or multiple, they can cause serious complications such as intestinal obstruction, ischemia, necrosis, fistula, perforation, and even death. This study aims to detail the complications and treatment approaches associated with magnet ingestion in children.Materials and Methods. In our study, we conducted a retrospective analysis of all cases involving the ingestion of a magnet along with a second metal object at two training and research hospitals in our province, which admit pediatric patients, between the years of 2013 and 2023.Results. A total of 42 patients had a history of magnet ingestion, with the number of ingested magnets ranging from 1 to 41. The median magnet size was 11 mm (range: 5.5-17.5 mm) and the median time to presentation was 24 hours (range: 3-48 hours). Thirteen patients (30.9%) required either endoscopic or surgical intervention to extract the magnets or address complications. Endoscopy was performed on eight patients, while surgical intervention was required for five patients. Among those who underwent surgery, four experienced complications, including intestinal perforation, ileoileal fistula, and internal herniation. Notably, no fatalities occurred following intervention. There was no statistically significant difference in age or magnet size between the interventional and non-interventional groups. However, the length of hospital stay was significantly longer in the interventional group compared to the non-interventional group (P
Keywords: magnet; foreign body; children; endoscopy; surgery